Penerapan Model Pembelajaran Active Learning Tipe Card Sort Terhadap Hasil Belajar IPA Siswa Kelas V SD Negeri Lonrong Kecamatan Bajeng Kabupaten Gowa - Khaerunnisa Khaerunnisa; Nurlina Nurlina; Hilmi Hambali (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research aims to determine the learning outcomes of class V students at Lonrong State Elementary School, Bajeng District, Gowa Regency in science learning after implementing the Card Sort Type Active Learning Model on Science Learning Results for Class V Students at Lonrong State Elementary School, Bajeng District, Gowa Regency. This research uses a pre-experimental quantitative research method involving one class as a focus class using a One Group Pretest-Posttest Design. The population in my research was class V students with a total of 20 students at Lonrong State Elementary School, Bajeng District, Gowa Regency. The sampling technique used was using only the experimental group without a control (comparison) group. The author took samples using total sampling techniques or saturated samples. So the sample size for this research is all fifth grade students at Lonrong State Elementary School, Bajeng District, Gowa Regency. The instruments used were student observation sheet instruments and science learning outcomes tests in the form of multiple choice questions to measure student learning outcomes with Pretest and Posttest. The results of the research show that the science learning outcomes of students in class V of Lonrong State Elementary School, Bajeng District, Gowa Regency, descriptive statistical analysis data revealed that after implementing the Card Sort Type Active Learning Model, the average score on the Pretest was 45, which is in the very low category with the number of students not 16 students completed, namely 80% and 4 students completed, namely 20%. Meanwhile, the average on the PostTest, namely 68.05, is in the medium category with the number of students who did not complete 4 people, namely 20% and 16 students who completed it, namely 80%. The average score on the PostTest is higher than the average score on the Pretest. Meanwhile, the average in the n-gain test was 0.41, which means it is in the medium category. So it can be concluded that the application of the Card Sort Type Active Learning Model to student learning outcomes in class V science learning at Lonrong State Elementary School, Bajeng District, Gowa Regency has increased.